2019
DOI: 10.1055/s-0039-1678707
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-Dependent Effects on Purinergic P2Y1 Receptor Expression

Abstract: Chronic treatment with aspirin in healthy volunteers (HVs) is associated with recovery of adenosine diphosphate (ADP)-induced platelet activation. The purinergic P2Y1 receptor exerts its effects via a Gq-protein, which is the same biochemical pathway activated by thromboxane-A2 receptor. We hypothesized that recovery of ADP-induced platelet activation could be attributed to increased P2Y1 expression induced by chronic aspirin exposure. We performed a multi-phase investigation which embraced both in vitro and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Our group recently demonstrated a correlation between MRP4 overexpression and P2Y1 overexpression in platelets [21]. Our findings suggest that both the enhancement of P2Y1 receptors and MRP4 overexpression in platelets are involved in HARPR.…”
Section: Discussionsupporting
confidence: 66%
“…Our group recently demonstrated a correlation between MRP4 overexpression and P2Y1 overexpression in platelets [21]. Our findings suggest that both the enhancement of P2Y1 receptors and MRP4 overexpression in platelets are involved in HARPR.…”
Section: Discussionsupporting
confidence: 66%
“…blood samples processing within 6 hours; absence of pharmacological treatments before symptoms onset and sample collection) as well as exclusion criteria (as reported in the Methods Section, we excluded all the STEMI patients under anti-thrombotic/anti-coagulant treatment and/or anti-platelet drugs [except aspirin, which is mandatory based on current guidelines] before the time of hospital admission) adopted generated the solid evidence reported. Even if data from the literature reported that aspirin could affect mRNA and protein expression of megakaryocytes and platelets 3436 , our results unequivocally distinguished STEMI patients from healthy donors (all without aspirin treatment) and from SCAD patients (all on aspirin treatment). Therefore, we believe that aspirin did not interfere with the concurrent differential expression of the five identified genes.…”
Section: Discussionmentioning
confidence: 44%